Synergistic Integration of Modular Four-Channel 50 kW WPT System: Enhancing Fast EV Charging and PMSM Drive Integration - Lakshmi, Kambampati; Muni, T. Vijay; Veerendra, A. S.; Kishore, D. Ravi; Norazlianie, Sazali; Kadirgama, Kumaran (Akademia Baru, 2026)
This paper presents an innovative approach to electric vehicle (EV) charging and propulsion system integration through the development of a Modular Four-Channel 50 kW Wireless Power Transfer (WPT) System with Decoupled Coil Design. The system architecture is designed to facilitate rapid charging of EV batteries while also enabling a seamless transition to a Permanent Magnet Synchronous Motor (PMSM) drive application post-charging. The decoupled coil design ensures efficient power transfer while minimizing electromagnetic interference. Leveraging this integrated solution, the charging process is optimized for speed and reliability, enhancing the EV user experience. Furthermore, the seamless transition to the PMSM drive application allows for immediate utilization of the charged EV battery for propulsion, ensuring maximum efficiency and functionality. The system delivers 50 kW power with 97% DC-to-DC efficiency over a 200 mm airgap and demonstrates balanced tolerance to misalignment. MATLAB/simulation validation demonstrates the effectiveness of the proposed system in achieving fast EV charging and smooth integration with the PMSM drive application, thereby offering a promising solution for future electric vehicle technology advancement.